SURVEY KUNJUNGAN IMUNISASI ANAK USIA 0 – 2 TAHUN DI PUSKESMAS SIKUMANA - Ummu Zakiah (STIKes CHMK, 2019)
Immunization is one of the effective ways to prevent transmission of the disease and plays an important role in tackling health problems. Immunization provides benefits so that children are not easily contracted by infection, do not easily suffer pain, and prevent the possibility of death due to an illness. Regulation of the Minister of Health number 12 of 2017 concerning the implementation of immunization states that immunization services can be carried out in buildings such as in health centers and outside buildings including Posyandu. The purpose of this study was to find out immunization visits of children aged 0 to 2 years at the sikumana health care center. This research is a quantitative research using descriptive method. Sampling using accidental sampling technique. The number of samples was 46 parents of infants who received immunization services at Sikumana Health care Center. The results showed that 84.8% of respondents chose to receive immunization services at the Puskesmas. Based on the reasons for choosing immunization services at Sikumana health care center, 41% of respondents gave reasons that they were not aware of other health facilities for immunization services and 42.8% of respondents in Desember 2019 chose to get immunization services at Sikumana health care center because of the Posyandu there is no vaccine. Based on the results of this study, it is necessary to increase the promotion efforts on health services at the Posyandu so that all people can find out the basic health services available at the Posyandu and need to improve the quality of table V services or health care service tables at the Posyandu by ensuring the availability of vaccines at the posyandu. Keywords: Immunization, Vaccines, IHC .